Serangan Hacking Tools sebagai Ancaman Siber dalam Sistem Pertahanan Negara (Studi Kasus: Predator) - Amelia Widya Octa Kuncoro Putri; Abdul Razzaq Matthew Aditya; Desta Lesmana Musthofa; Pujo Widodo (Global Political Studies Journal, 2022)
When we're talking about national defense, the meaning is currently expanding in line with the times. The advancement of technology today can be seen from the massive use of smartphones in the world. However, technological developments also followed by the potential for cybercrime which is also increasingly sophisticated, currently cybercrime is evolving from just password guessing to tools. One example of a tool is predatory spyware. Attacks with sophisticated equipment such as predatory hacking tools can threaten cyber security in the national defense system. Therefore, literature is needed to uncover and overcome cyber attacks and hacking threats to national defense. The method used in this article is descriptive qualitative research method. The results of this research are first, the cyber attack method consists of cyber espionage, vandalism, sabotage, and power grid attacks. Second, the operand mode of cybercrime consists of two ways, physically hacking and logically hacking. Third, predatory spyware is a hacking tool developed by the company Cytrox that can record the user's cellphone activity and has potential to threaten the country's cyber defense. Fourth, the biggest potential loss from predatory spyware is the dissemination of strategic information from the state to other parties that can threaten state security.